2022
DOI: 10.3389/fphy.2022.1034783
|View full text |Cite
|
Sign up to set email alerts
|

A scale space theory based motion correction approach for dynamic PET brain imaging studies

Abstract: Aim/Introduction: Patient head motion poses a significant challenge when performing dynamic PET brain studies. In response, we developed a fast, robust, easily implementable and tracer-independent brain motion correction technique that facilitates accurate alignment of dynamic PET images.Materials and methods: Correction of head motion was performed using motion vectors derived by the application of Gaussian scale-space theory. A multiscale pyramid consisting of three different resolution levels (1/4x: coarse,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Overall, these findings suggest that low-dose FDG-PET/CT imaging may be a valuable option for reducing radiation exposure in FDG-PET/CT imaging for composing a normative database of healthy control values [9]. Our SUV BW readouts for both STD and LD acquisitions were similar to published literature values [22][23][24].…”
Section: Volume Of Interestsupporting
confidence: 79%
See 2 more Smart Citations
“…Overall, these findings suggest that low-dose FDG-PET/CT imaging may be a valuable option for reducing radiation exposure in FDG-PET/CT imaging for composing a normative database of healthy control values [9]. Our SUV BW readouts for both STD and LD acquisitions were similar to published literature values [22][23][24].…”
Section: Volume Of Interestsupporting
confidence: 79%
“…The technological innovations of recent years, culminating in the introduction of total-body (TB) PET/CT systems [5], have brought continuous improvements in system performance and sensitivity [6,7] and consequently expanded PET/CT imaging to new research areas. For instance, the advent of extended axial fieldof-view PET systems allows the simultaneous and quantitative imaging of multiple distant organs, thereby providing the possibility to investigate multi-organ metabolic information and detect potential anomalies from normal metabolic activity patterns [8,9]. To visualize and quantify metabolic aberrations, it is necessary to establish a normative, organ-or voxel-wise, database based on the images derived from healthy controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we embed the images in gaussian scale space and conduct the alignment in multiple resolutions. Doing so increases image similarity between early and late frames by suppressing highfrequency information in both frames (24). Using this approach, we found that motion could be corrected for frames later than about 2 min after injection for tracers such as 18 F-FDG and 18 F-fluciclovine.…”
Section: Scale Space Theory For Dynamically Changing Uptake Patternmentioning
confidence: 93%